Prevalence, Phenotypic Characterization and Antibiogram of Uro-pathogenic Escherichia coli among Patients attending a Tertiary Institution Teaching Hospital in Katsina Metropolis, Nigeria - M. A. Garga; A. Ado; I. Mzungu; A. K. Suleiman; H. Abdullahi (Journal of Applied Sciences and Environmental Management)
The objective of this paper was to investigate the prevalence, phenotypic characterization and antibiogram of uro-pathogenic Escherichia coli (UPEC) among patients attending a Tertiary Institution Teaching Hospital in Katsina Metropolis, Nigeria using appropriate standard methods with one hundred and fifty (150) urine samples. Data obtained reveals that 78(52%) yielded growth with 25(16.67%) UPEC prevalence from the study population. The highest prevalence based on age was observed in the age group 31-40 years (35.9%). Based on gender, females were observed to have high UTIs prevalence (55.55%) than males. UPEC isolates were found to be highly susceptible to Nitrofurantoin and Imipenem while notable UPEC resistance were observed with ERY, CAZ, CRX, and AMP. Multiple drug resistant index (MARI) ranged from 0.3 to 0.7 in FTHK patients indicating the existence of high multi-drug resistance UPEC. Routine surveillance on UPEC among UTI patients is recommended.